SOCIAL AND MORAL RESPONSIBILITY IN ERIC TILL'S LUTHER MOVIE (2003): A SOCIOLOGICAL APPROACH - Setiawan, Hanif (2011)
The main aim of this study is to find how Social and moral responsibility is reflected in Eric Till's Luther by correlating its structural elements and social historical background of German in sixteenth century. Indeed, literature and sociology are bounded each other due to the assumption that the appearance of literary work is in social emptiness. This study uses qualitative method in which the data are taken from both primary and secondary data source in form of words, sentence and phrases. Primary data source is Eric Till's Luther meanwhile secondary data sources are other sources related to the primary data. Data collecting method in this study is library research, and in analyzing the data the researcher employs descriptive analysis. The outcomes of this study are as follows: (1) Eric Till's Luther reflects social condition occurred in sixteenth century of German. (2) Eric Till's depicts social and moral responsibility that creates in Luther (3) Luther is Eric Till's satire and criticism toward unbalance situation and condition that can be found in character's characterization, narration and dialogue.